Bioactive glass ions for in vitro osteogenesis and microvascularization in gellan gum‐collagen hydrogels. Issue 4 (31st August 2019) - Vuornos, Kaisa; Huhtala, Heini; Kääriäinen, Minna; Kuismanen, Kirsi; Hupa, Leena; Kellomäki, Minna; Miettinen, Susanna
Abstract: Lack of bone grafts appeals for bone augmentation solutions. We aimed at osteogenic differentiation of human adipose stem cells (hASCs) and microvascularization in coculture with human umbilical vein endothelial cells (HUVECs) embedded in three‐dimensional (3D) gellan gum (GG) and collagen type I (COL) hydrogel mixture. We compared endothelial growth medium‐2 (EGM‐2) and bioactive glass extract‐based endothelial and osteogenic medium (BaG EM‐OM) for vascularized bone‐like graft development in vitro . Cell viability, cell number, and osteogenic and endothelial gene expression were analyzed. Mineralized hydroxyapatite residues, immunocytochemical staining of endothelial marker CD31 production and late osteogenic marker osteocalcin were imaged. With both media, good cell viability was observed within 3D hydrogel. EGM‐2 condition induced significantly higher cell number compared to BaG EM‐OM condition at both 7 and 14 days. Interestingly, both media supported osteogenic as well as endothelial marker gene expression. Moreover, formation of reticulated cellular structures was observed in both EGM‐2 and BaG EM‐OM conditions. However, hydroxyapatite mineralization and strong osteocalcin staining were detected only in BaG EM‐OM condition. Importantly, strong production of CD31 and elongated tube‐like structures were apparent in EGM‐2 culture alone. In conclusion, we demonstrated efficient hASC osteogenic differentiation and microvessel‐like network formation in coculture with HUVECs.